2023
DOI: 10.3390/rs15061522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GEDI LiDAR Data Capability for Forest Canopy Height Estimation over Broadleaf and Needleleaf Forests

Abstract: The GEDI LiDAR system was specifically designed to detect vegetation structure and has proven to be a suitable tool for estimating forest biophysical parameters, especially canopy height, at a global scale. This study compares the GEDI relative height metric (RH100) over different forest types, especially deciduous broadleaf and evergreen coniferous located in Thuringia, Germany, to understand how the forest structural differences affect the GEDI height estimation. A canopy height model that was produced using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…When the data were closer to 1, it indicated high quality. Usually, the value was set to be greater than 0.95 in dense forest areas [28]. After quality filtering, 52,366 footprints were obtained (Figure 3b).…”
Section: Gedi Data and Processingmentioning
confidence: 99%
“…When the data were closer to 1, it indicated high quality. Usually, the value was set to be greater than 0.95 in dense forest areas [28]. After quality filtering, 52,366 footprints were obtained (Figure 3b).…”
Section: Gedi Data and Processingmentioning
confidence: 99%
“…Similar to the pattern observed with terrain height being influenced by terrain slope, canopy height accuracy from GEDI decreases significantly when terrain slope is steep, while ICESat-2 maintains high canopy height accuracy. This could be attributed to the fact that increasing slope steepness results in more overlap between ground and canopy returns in GEDI data [27,28], which in turn affects the extraction of canopy height. In contrast, ICESat-2's ground and canopy-top photons are relatively less affected by terrain slope, contributing to its higher canopy height extraction accuracy in steep terrain.…”
Section: Canopy Height Retrievalmentioning
confidence: 99%
“…Plausible reasons are the novel data characteristics of GEDI (sampling mission, variety of datasets available) and the maximum latitudinal coverage of 52 • N, thus challenging Germany-wide studies. Since March 2023, several studies using GEDI data covering Germany have been published [36,[155][156][157]. A further increase in studies making use of GEDI data might be promoted through the confirmed mission extension from end of 2024 to 2031 [158] and upcoming spaceborne long-wavelength SAR (Synthetic Aperture Radar) missions (BIOMASS, NISAR).…”
Section: Future Developmentsmentioning
confidence: 99%